Thermal and phase studies of magnesium oxide synthesized by using two types of gelating agent / Ummi Shafikah Ahmad Basa - Ahmad Basa, Ummi Shafikah (Faculty of Applied Sciences, 2010)
Magnesium oxide (MgO) nanopowder was synthesized by using sol-gel method. The starting materials were used are magnesium acetate tetrahydrate and two types of gelating agent which are oxalic acid and tartaric acid with ethanol as a solvent. The annealing treatment involves at different time which at 1, 3 and 6 hours with different temperature at 550, 600 and 650°C. The magnesium oxide nanopowders were characterized by using thermal gravimetric analysis (TGA) and X-ray powder diffraction (XRD). The thermal behavior for both gelating agents showed their stability at 500°C and 450°C for oxalic acid and tartaric acid respectively. All products were showed their purity when all of the peaks occur at a single phase in XRD spectra.